SELF-LOVE MANAGEMENT AS A STRATEGY FOR REDUCING BURNOUT AMONG PRIVATE UNIVERSITY LECTURERS IN MEDAN - Mega Sanjaya; Albert; Arif Fachrian; Manda Dwipayani Bhastary; Tyus Windi Ayuni (CV. Radja Publika, 2026)
Burnout among lecturers has become an important concern in private higher education due to increasing teaching, research, administrative, and institutional responsibilities. This study examines the effect of self-love management on lecturer burnout and evaluates its implications for performance and well-being among private university lecturers in Medan, Indonesia. Self-love management was measured through self-awareness, self-care, emotional regulation, work-life balance, and self-acceptance, while burnout was assessed through emotional exhaustion, depersonalization, and reduced personal accomplishment. The study employed a quantitative explanatory design involving 237 respondents selected using proportionate stratified random sampling. Data were analyzed using descriptive statistics, reliability testing, Pearson correlation, and multiple regression. The results showed that self-love management was negatively associated with burnout and positively associated with lecturer performance and well-being. Emotional regulation and work-life balance were the most influential dimensions in reducing burnout. In contrast, organizational stressors positively contributed to burnout. The combined model explained 49.6% of the variation in lecturer burnout. These findings indicate that burnout reduction requires both individual self-management strategies and institutional policies addressing workload, emotional support, and work-life balance.